2021
DOI: 10.1002/iub.2504
|View full text |Cite
|
Sign up to set email alerts
|

LEAP‐2/ghrelin interplay in adult growth hormone deficiency: Cause or consequence? A pilot study

Abstract: Ghrelin and its endogenous antagonist liver‐expressed antimicrobial peptide‐2 (LEAP‐2) are involved in GH secretion and glucose/lipids metabolism. LEAP‐2 expression in conditions of metabolic impairment may be upregulated, usually pairing with a concomitant reduction in ghrelin secretion. Adult growth hormone deficiency (aGHD) is characterized by insulin resistance, weight gain, and increased fat mass. Therefore, the primary endpoint of this cross‐sectional observational pilot study was to compare circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…One potential explanation of the limited impact of body weight is that none of the participants in current study carried a diagnosis of obesity and, instead, had BMIs within a lower and relatively narrow range. In addition, participants with metabolic disorders such as diabetes, hyperlipidemia, and hypercholesterolemia, as well as thyroid and hypothalamic disorders that may potentially affect LEAP2 regulation ( 72 , 73 ), were excluded. Whether this age-related upward shift in the LEAP2/ghrelin balance occurs as a natural defense against potentially deleterious, age-associated metabolic changes — perhaps at the expense of cognitive decline — is an interesting thought experiment.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation of the limited impact of body weight is that none of the participants in current study carried a diagnosis of obesity and, instead, had BMIs within a lower and relatively narrow range. In addition, participants with metabolic disorders such as diabetes, hyperlipidemia, and hypercholesterolemia, as well as thyroid and hypothalamic disorders that may potentially affect LEAP2 regulation ( 72 , 73 ), were excluded. Whether this age-related upward shift in the LEAP2/ghrelin balance occurs as a natural defense against potentially deleterious, age-associated metabolic changes — perhaps at the expense of cognitive decline — is an interesting thought experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, plasma concentrations of IGF-1 and LEAP2 increase during the pubertal growth spurt, and show a positive correlation in girls. 31 However, serum concentrations of LEAP2 and IGF-1 are not correlated in adults, 47,48 indicating that the link between these peptide hormones is dynamic and depends on the life stage. In this regard, it is interesting to mention that IGF-1 concentration is significantly associated with BMI in young (20-58 years) and old (67-86 years)…”
Section: Snpmentioning
confidence: 99%
“…In addition to metabolic diseases, it has also been found to be elevated in autoimmune diseases such as rheumatoid arthritis and is associated with inflammatory markers. Compared to healthy controls, the LEAP-2/Ghrelin ratio increases in patients with growth hormone deficiency [ 16 ]. Studies have also found that LEAP-2 is highly expressed in girls, especially those in the developmental stage (compared to males and pre-developmental females) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%